Sexual behaviour, sperm quantity and quality after short-term streptozotocin-induced hyperglycaemia in rats - Scarano, W. R.; Messias, A. G.; Oliva, S. U.; Klinefelter, G. R.; Kempinas, W. G. (Blackwell Publishing, 2006)
Studies of diabetes mellitus in the streptozotocin rat model suggest that sexual dysfunctions may result from diabetes-induced alterations of the neuroendocrine-reproductive tract axis. Our investigation was performed to better define the effects of short-term hyperglycaemia on rat epididymal sperm quantity, quality and transit time, using both natural mating and artificial in utero insemination protocols. Male rats were made diabetic with streptozotocin (sc, 40 mg/kg), whereas controls received vehicle. Sexual behaviour was tested after 15 days and sperm fertilizing ability was checked 22 days after the injection through natural mating and artificial in utero insemination. Other parameters such as daily sperm production, testosterone levels, as well as sperm morphology and motility were also investigated. Fifty per cent of the diabetic animals showed no copulatory behaviour during tests and the number of animals reaching ejaculation was smaller in the diabetic group when compared with the control group (33% vs. 83%). Diabetes resulted in decreased body and reproductive organ weights, as well as diminished sperm counts in the testis and epididymis, that were associated with diminution of plasmatic testosterone levels. After natural mating, there was a decrease in the fertility in the diabetic adult male rats (25.5%) compared with control animals (81.5%). However, distal cauda epididymal sperm from diabetic rats displayed normal fertilization ability (91.5%) using in utero insemination. There were no effects of hyperglycaemia on sperm transit time in the epididymis and on spermatogenesis. Our results indicate that diabetes mellitus produces reproductive dysfunction, but does not compromise sperm fertilizing ability in the cauda epididymis in this experimental model.
Keywords: diabetes mellitus; epididymis; fertility; rat; sperm; streptozotocin